مفهوم الخطأ وصوره بين القانون الجنائي والفقه الإسلامي - Suza'i, Faruk Salami; Arif, Arif Ali (The Scientific Institute for Advanced Training and Studies, 2016)
This study determines the concept of mistake and its types in the criminal Iranian law and Islamic jurisprudence, it is indicated that mistake in law is defined as any action or omission that perpetrator has not done it intentionally to commit a crime, and the owner causes a loss or injury, however, it is impossible that he may know that the consequence of his action may causes damage to someone although he could prevent it. Islamic jurisprudence’s definition of the concept of mistake is: occurrence of an event contrary to the will of the perpetrator that is not intentionally. This study introduces different kinds of mistakes. In terms of law, they include the lack of caution and care, negligence and lack of attention. lack of skill, and disobeying the rules and regulations. However, different types of mistakes in Islamic jurisprudence are more extensive than in law. The author tried to address the conformity between the concept of mistake and its different types in criminal Iranian law and Islamic jurisprudence. A comparative method is used analyzing the issue related to the concept of mistake and its types are discussed and then a comparative study is concluded.